Parental Worrying, Family Functioning, and Quality of Life During the COVID-19 Pandemic. Issue 2 (March 2022) - Taha, Asma A.; Azar, Najood Ghazi; Eisen, Aaron M.; Abdul-Rahman, Hana Q.; Hanes, Douglas A.
Abstract : Background: The 2019 novel coronavirus pandemic has affected many aspects of American life, with reported increases in parental anxiety and adverse health outcomes among children. However, it is unknown how family functioning and parental anxiety may be associated with child health outcomes during this pandemic. Objectives: The aim of this study was to explore associations among parental worrying, family functioning, and the health-related quality of life (HRQoL) of middle and high school-aged children in the United States during the 2019 novel coronavirus pandemic. Methods: Ninety-three parent–child dyads were recruited via snowball sampling through the WhatsApp messenger from December 2020 to February 2021 in this exploratory cross-sectional study. Each family completed a series of self-report measures, including the General Functioning Scale–Family Assessment Device and the Worry Domains Questionnaire for parent respondents and the KIDSCREEN-10 for child respondents. A hierarchical regression analysis was performed to examine effects of parental worrying and family functioning on the HRQoL of middle and high school-aged children. Results: Lower levels of parental worrying and better family functioning predicted better child HRQoL, whereas parental worrying was associated with worse family functioning. The relationship between family functioning and child HRQoL did not differ by levels of parental worrying. Increased child age and parental education were associated with worse child HRQoL. Discussion: The high socioeconomic status sample reported healthy family functioning during the 2019 novel coronavirus pandemic. Family functioning appears to improve child HRQoL consistently, even as parental worrying increases or decreases, although increased worrying would likely decrease family functioning and child HRQoL. The inverse relationships of parental educational attainment with family functioning and child HRQoL are surprising; they may be due to pandemic circumstances and the nature of the sample being high-socioeconomic status families with middle and high school-aged children. Abstract : Supplemental digital content is available in the text.